Sea turtle management in three conservation areas of West Sumatera using EVIKA approach - Deshan, Farah; Jabbar, Meuthia Aula; Ruchimat, Toni (JURNAL MINA SAINS, 2025)
Sea turtles are keystone species in coastal ecosystems, playing an essential role in maintaining ecological balance by regulating the population of certain marine organisms and sustaining the quality of critical habitats such as seagrass beds and coral reefs. Their presence not only reflects the health of marine ecosystems but also serves as a key indicator of the success of marine conservation initiatives. This study evaluates the effectiveness of conservation area management in three sites in West Sumatera Province using the Evaluation of Marine Protected Area Management Effectiveness (EVIKA) framework, namely the Pieh Marine Protected Area on Pandan Island, Karabak Ketek Island, and the Ampiang Parak Conservation Area. A descriptive analysis was applied to assess the performance of each EVIKA criterion and indicator. The results show that the Pieh Conservation Area achieved a sustainable management status with the highest score in the input component, while Karabak Ketek Island and Ampiang Parak were categorized as optimally managed. The effectiveness of management across these areas is influenced by several key factors, including the strength of legal frameworks, the availability and competence of human resources, institutional capacity, and the level of community participation. This study recommends enhancing multi-stakeholder collaboration, strengthening the role of community-based monitoring groups (pokmaswas), and implementing participatory monitoring systems that are community-driven and adaptive to the dynamic changes of coastal environments.